Toward a Sustainable System of Wastewater Treatment Plants in Chile: A Multi-Objective Optimization Approach - Vasquez-Perez, O; Espinoza-Perez, A; Jorquera-Bravo, N (Springer, 2022)
Over the past fifty years the population of the world has doubled, while resources as water have become increasingly scarce. In particular, water consumption has far exceeded the available of this resource in some regions of the world. In order to address the above problem, the possibility of reusing grey water by installing wastewater treatment plants could be a suitable alternative for several developing countries. This paper seeks to find the best configuration for these facilities in Chile by considering the economic and environmental aspects conjoint to the social dimension. The problem is modeled as a multi-objective optimization including: minimizing costs, minimizing environmental impact, maximizing phosphorus extraction from wastewater and maximizing the number of workers to be required with the goal of analyzing the sustainability of the system. To find the Pareto frontiers of multi-objective problem, a resolution framework based on an adaptation of elitist non-dominated sorting genetic algorithm (NSGA-II) is provided for the problem. From the obtained results, the non-dominated solutions and a compromise solution are computed, reporting configuration alternatives that integrate the three sustainability dimensions, the economic, the environmental and the social as objectives for the design for a sustainable system of wastewater treatment plants. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.